2017
DOI: 10.14720/aas.2017.109.2.22
|View full text |Cite
|
Sign up to set email alerts
|

High salicylic acid concentration alters the electron flow associated with photosystem II in barley

Abstract: In this study, the effects of exogenously applied salicylic acid (0.5 and 5 mM SA) on the rates of photosystem II (PSII) activity was analysed in 4-week-old barley (Hordeum vulgare'Bahman') seedlings using chlorophyll (Chl) a fluorescence transient (OJIP) measurements. No evident changes in Chl and carotenoid contents as well as chlorophyll fluorescence transient curves were observed in either of the studied concentrations after 24 h of SA application. After 5 d, low SA concentration (0.5 mM) increased PSII ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…It suggested that IL 13 caused the PS II center damage leading to decreased excitation energy transfer from the antenna to the reaction center. 48 The damage to PS II center can be detected from the decreases in maximal PS II quantum yield F v /F m and the performance index PI abs . The values of F v /F m and PI abs of IL 13-treated leaves were decreased by 18% and 70%, respectively.…”
Section: The Herbicidal Mechanism Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It suggested that IL 13 caused the PS II center damage leading to decreased excitation energy transfer from the antenna to the reaction center. 48 The damage to PS II center can be detected from the decreases in maximal PS II quantum yield F v /F m and the performance index PI abs . The values of F v /F m and PI abs of IL 13-treated leaves were decreased by 18% and 70%, respectively.…”
Section: The Herbicidal Mechanism Studymentioning
confidence: 99%
“…It provided information about biophysical properties of the photosynthetic energy conversion and transport of electrons. [46][47][48][49][50][51] Some uorescence parameters were highlighted: (a) area: total complementary area between F o and F m (reecting the size of the plastoquinone pool); where F o is minimal uorescence when PSII RCs are all open, F m : maximal uorescence when PSII RCs are all closed; (b) the specic energy uxes per reaction center RC for absorbance (ABS/RC), for transport (ET 0 /RC), for trapping TR 0 /RC and for reduction (RE 0 /RC); (c) the phenomenological energy uxes per excited cross section for absorbance (ABS/CS m ), for transport (ET o /CS m ), for trapping (TR o /CS m ) and for reduction (RE 0 /CS m ); (d) the performance index:…”
Section: Ec 90 (Weeds)mentioning
confidence: 99%
“…Многочисленные авторы неоднократно рассматривали как теоретические аспекты, так и прак-тические возможности формирования наноостровковых покрытий посредством распада сплошных сверхтонких плeнок при термическом отжиге [3][4][5][6][9][10][11][12][13][14][15].…”
Section: теоретическая частьunclassified
“…The observed a large peak that demonstrates the major nanostructure of the films, while small narrow peaks are a proof for minor microcrystalline in the film matrix. It is seen that the intensity of the diffraction peak increases with increase of annealing temperature [24]. The absence of any intense peaks throughout the spectrum for PVA-In 2 O 3 hybrid thin films indicated the predominantly amorphous nature of the film [18,25].…”
Section: 2mentioning
confidence: 99%